THE SUPPLY CHAIN INNOVATION, SUPPLY CHAIN TRANSACTION COST, SUPPLY CHAIN RISK AND SUPPLY CHAIN RESPONSIVENESS AND THE SUPPLY BASE AND ITS COMPLEXITY - Thongrawd, Chairit; Mee-ngoen, Benjabhon; Jermsittiparsert, Kittisak (International Journal of Supply Chain Management, 2019)
The main objective of the study is to investigate the impact of the supply chain innovation, supply chain transaction cost, supply chain risk and supply chain responsiveness as antecedents of the supply base and its complexity. The study attempted to understand the way in which transaction costs, supplier responsiveness, supplier innovation, and supply risk are affected by the supply base complexity, and the study also expressed them in liner relationships. With the supply base complexity, it became easier to understand ways for managing supply base. Therefore, the study is among the pioneering studies on the issues. So, current study has used SEM-PLS as statistical tool to answer the research questions raised in this study and research objectives envisaged in the current study. The findings of the current study have provided support to with the hypothesized results. This study will be helpful for policymakers and researchers in examining the link between supply chain innovation, supply chain transaction cost, supply chain risk and supply chain responsiveness as antecedents of the supply base and its complexity.